THE EFFECT OF SHORT-TERM DEBT, LONG-TERM DEBT, TANGIBILITY, SALES GROWTH, FIRM SIZE, AND DEBT TO ASSET RATIO ON THE PERFORMANCE OF MANUFACTURING COMPANIES - Pradana, Ellen Agustin; Imelda, Elsa (International Journal of Application on Economics and Business, 2023)
This study aims to obtain empirical evidence regarding the effect of short-term debt, long-term debt, tangibility, sales growth, firm size, and debt to asset ratio on the performance of manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2021 period. The amount of data in this study was 243 samples with purposive sampling method. The test used in this study is the classical assumption test and uses multiple linear regression methods, and data processing using EViews 12 and IBM SPSS 26. The dependent variable in this study is company performance with the proxy Return on Asset (ROA), where the results obtained are sales growth has a positive effect on company performance, firm size and tangibility have a negative effect on company performance, and short-term debt, long-term debt, and debt to asset ratio have no negative effect on company performance.